2013
DOI: 10.4149/neo_2013_061
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hepatoma tumor growth by systemic administration of the phytotoxin gelonin driven by the survivin promoter

et al.

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of cancer worldwide. However, there is currently no effective therapy strategy in the clinical practice. Recombinant phytotoxin gelonin fused to other factors have been used to treat different cancers. But there have been no reports of gelonin gene therapy. In this study, we have constructed a recombinant plasmid which contained a tumor-specific survivin promoter to drive phytotoxin gelonin (pSur-Gel). And the cytotoxicity effects of pSur-Gel in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As a new form for cancer treatment, gene therapy has been used for certain cancers, and a number of clinical trials including phase I, II and III trials for various cancers are underway [ 6 , 7 ]. Recent gene therapy for HCC is still confined to pre-clinical laboratory investigations, focusing on single or multiple genes dysregulated/mutated in HCC cells [ 8 - 12 ]. Gene therapy exhibits synergistic antitumor ability when combined with radiotherapy or chemotherapy [ 13 - 16 ], However, mutations or aberrant expressions of those target genes are highly variable in HCC, the strategy targeting one or a few of alterations may only be effective for a small group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a new form for cancer treatment, gene therapy has been used for certain cancers, and a number of clinical trials including phase I, II and III trials for various cancers are underway [ 6 , 7 ]. Recent gene therapy for HCC is still confined to pre-clinical laboratory investigations, focusing on single or multiple genes dysregulated/mutated in HCC cells [ 8 - 12 ]. Gene therapy exhibits synergistic antitumor ability when combined with radiotherapy or chemotherapy [ 13 - 16 ], However, mutations or aberrant expressions of those target genes are highly variable in HCC, the strategy targeting one or a few of alterations may only be effective for a small group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, new strategies are required to address the resistance of HCC to apoptosis in order to improve the poor prognosis. Considerable attention has been directed towards investigating the effect of triggering apoptosis in HCC cells using natural products that stimulate DR-mediated apoptosis ( 31 ). In the present study, rocaglamide, a naturally occurring product, was demonstrated to sensitize TRAIL-resistant HCC cells to apoptosis through the suppression of c-FLIP in both in vitro and in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“… Bmi-1 36 gastric cancer, prostate cancer, glioma cancer, etc. Survivin 39 , 40 , 60 , 61 , 63 liver cancer, gastrointestinal cancer, gallbladder cancer, etc. HER-2 40 , 41 prostate cancer, breast cancer, pancreatic cancer, etc.…”
Section: Main Textmentioning
confidence: 99%